Catering skills setting the scene - Baden-Powell, Edwina; Garner, Simon; Lovering, Matthew; Video Education Australasia (Lawrenceville, NJ : Meridian Education Corp., 2009)
Immerses students in the world of commercial meal preparation, covering planning the menu, presentation skills, table settings, styles of service, and serving the meal.
Editor, Paul Sutherland ; narrator, Edwina Baden-Powell.
Keywords: Caterers and catering; Food service